2015
DOI: 10.1021/acs.cgd.5b01016
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Piroxicam Polymorphism in Solution Crystallization: Effect and Interplay of Operation Parameters

Abstract: Recently, new insights into crystallization prior to actual nucleation have shown interesting results for drugs showing differences in hydrogen bonding or orientation in various polymorphic forms. On the basis of this concept, piroxicam was chosen as a model compound because the two common forms, I and II, show hydrogen bonding between different parts of the molecules and differences in the orientation of molecules in the crystal lattice. The goal of this work is to explore how various methods of controlling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 22 publications
(42 reference statements)
8
29
0
Order By: Relevance
“…But since a change in initial concentration also changes the nucleation temperature, it is difficult to determine which of the two has the largest impact. Similar result has though, been observed in our previous work [15] where the crystallization of piroxicam from different acetone-water mixtures was investigated. The results showed a well-defined landscape of the two polymorphs of piroxicam depending on the initial concentration, where form 2 was produced at high solute concentrations and form 1 was formed at low concentration ranges as long as the acetone mass fraction of the solvent was kept below 95%.…”
Section: Figure 11 Cooling Trend and Ir Peak Height For Methanol 10°csupporting
confidence: 90%
See 2 more Smart Citations
“…But since a change in initial concentration also changes the nucleation temperature, it is difficult to determine which of the two has the largest impact. Similar result has though, been observed in our previous work [15] where the crystallization of piroxicam from different acetone-water mixtures was investigated. The results showed a well-defined landscape of the two polymorphs of piroxicam depending on the initial concentration, where form 2 was produced at high solute concentrations and form 1 was formed at low concentration ranges as long as the acetone mass fraction of the solvent was kept below 95%.…”
Section: Figure 11 Cooling Trend and Ir Peak Height For Methanol 10°csupporting
confidence: 90%
“…Although several works showed a link between the structure of the building units formed by the self-association of the molecules and the polymorphism of the nucleated crystals, we have discovered the complex nature of this structural link in the previous work regarding the crystallization of piroxicam. It has been observed in our previous work [15] that the solute concentration played a significant role in determining the polymorphism of piroxicam crystallized from acetone-water solutions.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…It was therefore decided to use seeding to have robust control of the product polymorphism. 19 . In some cases, the monohydrate form was also found during anti solvent experiments, although in very low quantities and only at 45°C.…”
mentioning
confidence: 99%
“…The form I crystals produced in the successful batch of anti solvent crystallization was used as seed crystals to investigate the feasibility of controlling the polymorphism of Piroxicam in cooling crystallization in the 2 L crystallizer system. ( It has been observed that seeding was effective for controlling polymorphism in the small scale 100 mL crystallizer 19 . For this reason seeded cooling crystallizations were conducted also to crystallize…”
mentioning
confidence: 99%